Promoção da saúde dos cuidadores de idosos: tecnologia educacional sobre saúde ocupacional - Oliveira, Anderson Belmont Correia de (2018)
Population aging has contributed to an increase in morbidity and a decrease in functional capacity, increasing the number of elderly people with some degree of dependence who need home care. Caring for an elderly person in a domestic environment can generate an overload on the family caregiver, which causes emotional, physical, economic and social disorders. Due to the unpreparedness of this caregiver his health can be put at risk, being able to thus present musculoskeletal alterations. Objectives: To identify the scientific production on health promotion of caregivers of the elderly; to develop an educational technology of the type guide on self-care in relation to occupational health for caregivers of the elderly; to verify the semantic, idiomatic, cultural and conceptual equivalences of the guide for caregivers of the elderly through a committee of judges and to carry out the semantic validation of the guide by a group of elderly caregivers. Method: This is a methodological study, whose proposal was to construct and validate semantically an educational technology of the guide type for the health promotion of caregivers of the elderly. Results: From the results obtained after analysis, two articles were outlined the first, an integrative review on the educational technologies for health promotion of caregivers of the elderly in which the rescued articles showed that the educational technologies were focused on the promotion of mental health of the caregiver in the aiming at guaranteeing a better care for the elderly, thus making it possible to identify an important scientific gap regarding the educational technologies used to promote the musculoskeletal health of caregivers of the elderly, as no studies on this care were found. The second article dealt with the elaboration and validation of an educational technology for health promotion of caregivers of the elderly. Conclusion: It is considered that the educational technology of the guide type "Health promotion of caregivers of the elderly: educational technology on occupational health", can contribute to the physical health of caregivers of the elderly in their caregiving, subsidize health professionals during activities of health education with caregivers of the elderly and fill an important scientific gap regarding health promotion in the physical overload experienced by caregivers of the elderly.